Community Service: Introduction to Accounting Basics for Quality Human Resources (HR) in the New Village, Pancur Batu District - Sipayung, Tri Dharma; Simanjuntak, Arthur; Purba, Dimita H.P; Sagala, Lamria; Simanjuntak, Grace Y; Panjaitan, Rike Yolanda; Situmorang, Duma Rahel; Silitonga, Ivo Maelina; Mesakh, Januardi; Sibarani, Apriani M (PT FORMOSA CENDEKIA GLOBAL, 2024)
Human Resources (HR) are fundamental assets in regional development and development. Community Service Activities in Baru Village, Pancur Batu District, aim to transform HR capacity through basic accounting training. This study uses a comprehensive extension method that includes lectures, discussions, practices, and evaluations to improve community financial literacy. The results of the activity showed a significant increase in understanding of accounting concepts, transaction recording skills, and awareness of the importance of structured financial management. Through a participatory approach, this activity succeeded in providing accounting knowledge that can encourage the development of individual and community capacity.